Psychological Readiness to Return to Sport at 6 Months Is Higher After Bridge-Enhanced ACL Restoration Than Autograft ACL Reconstruction: Results of a Prospective Randomized Clinical Trial. Issue 2 (9th February 2022) - Sanborn, Ryan M.; Badger, Gary J.; Proffen, Benedikt; Sant, Nicholas; Barnett, Samuel; Fleming, Braden C.; Kramer, Dennis E.; Micheli, Lyle J.; Yen, Yi-Meng; Murray, Martha M.; Christino, Melissa A.
Background: Previous clinical studies have shown that psychological factors have significant effects on an athlete's readiness to return to sport after anterior cruciate ligament (ACL) reconstruction (ACLR). Hypothesis: We hypothesized that patients who underwent bridge-enhanced ACL restoration (BEAR) would have higher levels of psychological readiness to return to sport compared with patients who underwent ACLR. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A total of 100 patients (median age, 17 years; median preoperative Marx activity score, 16) with complete midsubstance ACL injuries were randomized to either the BEAR procedure (n = 65) or autograft ACLR (n = 35 [33 hamstring and 2 bone–patellar tendon—bone]) and underwent surgery within 45 days of injury. Objective, functional, and patient-reported outcomes, including the ACL–Return to Sport after Injury (ACL-RSI) scale, were assessed at 6, 12, and 24 months postoperatively. Results: Patients who underwent the BEAR procedure had significantly higher ACL-RSI scores at 6 months compared with those who underwent ACLR (71.1 vs 58.2; P = .008); scores were similar at 12 and 24 months. Baseline factors independently predictive of higher ACL-RSI scores at 6 months were having a BEAR procedure and participating in level 1 sports prior to injury, explaining 15% of the variability in the scores. Regression analysis of baseline and 6-month outcomes as predictors indicated that the International Knee Documentation Committee (IKDC) score at 6 months explained 45% of the 6-month ACL-RSI variance. Subsequent analysis with IKDC excluded from the model indicated that decreased pain, increased hamstring and quadriceps strength in the surgical limb, and decreased side-to-side difference in anteroposterior knee laxity were significant predictors of a higher ACL-RSI score at 6 months, explaining 34% of the variability in scores. Higher ACL-RSI score at 6 months was associated with earlier clearance to return to sports. Conclusion: Patients who underwent the BEAR procedure had higher ACL-RSI scores at 6 months postoperatively. Better ACL-RSI scores at 6 months were related most strongly to higher IKDC scores at 6 months and were also associated with lower pain levels, better muscle recovery, and less knee laxity at 6 months. Registration: NCT02664545 (ClinicalTrials.gov identifier).